Access to Zero-Emission Vehicles for Low-Income and Disadvantaged Communities: Evidence from California - Yogaswara, Galih Bramudyas; Guan, Yanzhen (Nusantara Science and Technology Proceedings, 2025)
This study assesses California's Clean Cars for All (CC4A) program, which seeks to improve access to clean-energy vehicles for low-income residents and reduce emissions. The research examines two questions: (1) How effective is CC4A in reducing greenhouse gas emissions and improving air quality? and (2) What factors influence participants' choice of vehicle type—conventional, hybrid, plug-in hybrid (PHEV), or zero-emission vehicle (ZEV)? Using participant data from the California Air Resources Board (n=3,497) from January 2022 to June 2023, the study applies multinomial logistic regression to identify car choice determinants. Findings indicate that CC4A effectively reduces emissions. Higher-income participants are more likely to choose ZEVs or PHEVs, while larger households tend to select conventional vehicles, likely due to limited ZEV options for larger family needs. Participants in disadvantaged communities show a preference for PHEVs over ZEVs, with notable geographic variation—Bay Area residents prefer ZEVs, whereas Central Valley residents favor PHEVs. Key limitations include data gaps, such as missing participant age and education data, and underrepresented geographic areas. The study concludes that while CC4A promotes clean transportation, further steps could enhance program impact. Recommendations include reducing cost barriers for ZEVs, expanding charging infrastructure in low-income areas, and increasing affordable ZEV options for larger households. These insights support policymakers in improving clean transportation access for underserved communities.